Muscarinic receptors in gastric mucosa are increased in peptic ulcer disease. Issue 6 (June 1995) - Pfeiffer, A; Krömer, W; Friemann, J; Ruge, M; Herawi, M; Schätzl, M; Schwegler, U; May, B; Schatz, H
Abstract : Muscarinic receptors stimulate the secretion of acid pepsinogen and mucous in gastric mucosa. Whether muscarinic receptors are involved in the pathogenesis of benign gastric disease is unknown. Receptor changes in these conditions were therefore sought. An autoradiographic technique was developed to determine quantitatively muscarinic receptors in microtome sections of biopsy specimens obtained during gastroscopy. Muscarinic receptor density was mean (SEM) 18.4 (1.2) fmol/mg protein in the corpus and 8.9 (0.7) fmol/mg protein in the antrum (n = 53). Neither chronic nor active gastritis was associated with receptor changes in the antrum but chronic gastritis was associated with a receptor loss in the corpus. Patients with acute or recent duodenal or antral ulcers (n = 23) had significantly higher levels of muscarinic receptors in the corpus than controls (n = 25) (22.2 (1.5) v 16.9 (1.7) fmol/mg protein respectively (p < 0.025). These results suggest that muscarinic M3 receptor is overexpressed in duodenal ulcer disease and may play a part in its pathogenesis.